2013
DOI: 10.1029/2012jb009344
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of the Alpine Fault near Inchbonnie, New Zealand

Abstract: The transpressive Alpine Fault is the boundary between the Pacific and Australian plates across the South Island of New Zealand. Earthquakes on the Alpine Fault and related structures pose a serious risk to many urban centers, including the city of Christchurch. Although it is a major feature on satellite images, the Alpine Fault is a difficult target for surface studies along much of its length; it mostly traverses densely forested and mountainous terrain and where it occurs in the lowlands it is usually cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…To the best of our knowledge, a listric shape of the Alpine Fault is only reported in middle to lower crustal levels [ Stern et al , ; Townend et al , , and references therein]. From studies of the shallow subsurface, linear structures for the fault branches are preferred [ Kaiser et al , and Carpentier et al , ].…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, a listric shape of the Alpine Fault is only reported in middle to lower crustal levels [ Stern et al , ; Townend et al , , and references therein]. From studies of the shallow subsurface, linear structures for the fault branches are preferred [ Kaiser et al , and Carpentier et al , ].…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Several seismic experiments have aimed to image the Alpine Fault at shallow depths. At the northern section of the Alpine Fault, Carpentier et al [] observed disrupted seismic reflections down to a depth of 400 m, which were inferred to be caused by the Alpine Fault dipping at an angle of 70–80° to the southeast. Further north, Kaiser et al [, ] obtained ultrahigh‐resolution seismic images that clearly show a steeply (75–80°) dipping Alpine Fault in the upper 60 m of the sediments and also indicate a prolongation of this dipping fault down into the upper basement at depths of 150 m. However, they could not obtain clear images of the Alpine Fault within the basement itself.…”
Section: Introductionmentioning
confidence: 99%
“…15 km up valley from the present‐day lake margin (Fig. ; Carpentier et al ., ). The base of this lacustrine sediment unit is ca .…”
Section: Discussionmentioning
confidence: 97%
“…C. Schematic diagram illustrating the interpretation of the seismic profile by Carpentier et al . (). LB, Lake Brunner; LP, Lake Poerua.…”
Section: Discussionmentioning
confidence: 99%
“…1776-1781, doi: 10.1190 surface velocity models, such as P-wave tomography, can perform poorly on loose granular formations, due to their low quality factor, which causes high attenuation (Prasad et al, 2004;Carpentier et al, 2012). The poor quality factor of soft, uncompacted granular media affects indeed the propagation of SWs as well.…”
Section: Introductionmentioning
confidence: 96%